Cleaning of Floating Photovoltaic Systems: A Critical Review on Approaches from Technical and Economic Perspectives - Rafi Zahedi; Parisa Ranjbaran; Gevork B. Gharehpetian; Fazel Mohammadi; Roya Ahmadiahangar (Energies, 2021)
There are some environmental factors, such as ambient temperature, dust, etc., which cause a reduction in the efficiency of Photovoltaic (PV) systems. Installation of PV panels on the water surface, commonly known as Floating Photovoltaic (FPV) systems, is one solution to employ PV panels in a cooler environment, achieve higher efficiency, and reduce water evaporation. FPV systems open up new opportunities for scaling up solar generating capacity, especially in countries with high population density and valuable lands, as well as countries with high evaporation rates and water resources deficiency. Since the FPV system is an almost new concept, its cleaning techniques have not been comprehensively studied. While FPV systems are located on the surface of water resources and reservoirs, the water quality can limit the application of different cleaning techniques. Therefore, this paper investigates different techniques of FPV systems cleaning and categorizes them into water-based and water-free approaches. In addition, their cleaning frequencies, as well as economic aspects, are presented and discussed to determine their merits and demerits for using them in FPV systems.